The factors related to gastritis incident on santriwati 12-15 years old - Desak Noman Tri Bulan Trisna Wardhana; Makhfudli Makhfudli; Laily Hidayati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction : Gastritis is a gastrointestinal tract disease which is often found on community. In developing country, gastritis often occurs at young age. In Pondok Pesantren Assalafi Al Fitrah Surabaya, gastritis was the most cases on santriwati 12-15 years old. The factors related to gastritis were food pattern, stress, medication adherence, and the use of Non Steroid Anti Inflammatory Drug (NSAID). This study was aimed to investigate factors correlating with gastritis incident on santriwati 12-15 years old in Pondok Pesantren Assalafi Al Fitrah Surabaya.Method : Design used in this study was descriptive analytic design with cross sectional approach. The population was all santriwati 12-15 years old who got gastritis in September 2013. Total sample was 30 respondents, taken according to inclusion criteria. The independent variables were food pattern, stress, medication adherence, and the use of Non Steroid Anti Inflammatory Drug (NSAID). The dependent variable was gastritis incident. Data were collected using structured questionnaire.Result : Data were then analyzed using Spearman’s rho test with level of significance < 0,05. Result showed that gastritis incident did have correlation with food pattern (ρ = 0,000), stress (ρ = 0,031) and medication adherence (ρ = 0,000). The use of Non Steroid Anti Inflammatory Drug (NSAID) has no correlation with gastritis incident (ρ = 0, 171).Discussion : It can be concluded that gastritis incident has correlation with food pattern, stress, and medication adherence, but has no correlation with the use of Non Steroid Anti Inflammatory Drug (NSAID). Further studies should involve larger respondents and better measurement tools to obtain more accurate results.